Association between stressful life events and exacerbation in multiple sclerosis: a meta-analysis. Issue 7442 (19th March 2004) - Mohr, David C; Hart, Stacey L; Julian, Laura; Cox, Darcy; Pelletier, Daniel
Abstract: Objective To quantify the association between stressful life events and exacerbations of multiple sclerosis. Data sources PubMed, PsychInfo, and Psychological Abstracts searched for empirical papers from 1965 to February 2003 with terms "stress", "trauma", and "multiple sclerosis". Review methods Three investigators independently reviewed papers for inclusion/exclusion criteria and extracted the relevant data, including methods, sample statistics, and outcomes. Results Of 20 studies identified, 14 were included. The meta-analysis showed a significant increase in risk of exacerbation in multiple sclerosis after stressful life events, with a weighted average effect size of d = 0.53 (95% confidence interval 0.40 to 0.65), P < 0.0001. The studies were homogenous, q = 16.62, p = 0.22, i 2 = 21.8%. Neither sampling nor study methods had any effect on study outcomes. Conclusions There is a consistent association between stressful life events and subsequent exacerbation in multiple sclerosis. However these data do not allow the linking of specific stressors to exacerbations nor should they be used to infer that patients are responsible for their exacerbations. Investigation of the psychological, neuroendocrine, and immune mediators of stressful life events on exacerbation may lead to new behavioural and pharmacological strategies targeting potential links between stress and exacerbation.